Karjalan Pyhäjärven vesien ja vesiluonnon suojelusuunnitelma - Kukkonen, Minna; Kiiski, Jaana; Luotonen, Hannu; Niinioja, Riitta (Pohjois-Karjalan ympäristökeskus, 2003)
Alueelliset ympäristöjulkaisut 319